2015
DOI: 10.25190/rec.v4i2.1422
|View full text |Cite
|
Sign up to set email alerts
|

Docência E Adoecimento: Uma Investigação Para Um Tema (Re)descoberto

Abstract: Uma das profissões mais antigas do mundo, a troca de conhecimento entre mestres e aprendizes (processo ensino-aprendizagem), com mudanças, tanto no cenário como no comportamento ou no próprio sistema educacional do qual somos usuários hoje, vemos algumas consequências negativas. Através de uma pesquisa percebeu-se diante dos atestados médicos dos professores, o quão ausentes estão os mesmos de seu ambiente de trabalho. Não simplesmente lesados em sua saúde física, mas principalmente em sua saúde mental, o que … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a study related to teaching and its illness, it was found that the possible causes of psychopathology are multiple and complex and consider the following factors that may influence these indices: the challenges of the formation and exercise of the profession, the demands of the educational system and the parents of students, the insecurity and violence of working with socially vulnerable publics, financial insecurity, the devaluation of the profession, and events involving affective relationships, whether family or otherwise 29 .…”
Section: Resultsmentioning
confidence: 99%
“…In a study related to teaching and its illness, it was found that the possible causes of psychopathology are multiple and complex and consider the following factors that may influence these indices: the challenges of the formation and exercise of the profession, the demands of the educational system and the parents of students, the insecurity and violence of working with socially vulnerable publics, financial insecurity, the devaluation of the profession, and events involving affective relationships, whether family or otherwise 29 .…”
Section: Resultsmentioning
confidence: 99%